Delayed rupture of the mitral valve complicating blunt chest trauma. - Farmery, A D (1998)
A case is described of acute torrential mitral regurgitation resulting from avulsion of both papillary muscles 12 hours after a blunt chest and abdominal injury. The intensive care and surgical management are discussed.